Studi Doking Molekuler Perbandingan Evektivitas Senyawa Dari Buah Morinda Citrifolia L Sebagai Antikanker: Molecular Docking Studies of comparison the effectiveness compounds from Morinda citrifolia L. fruits as an anticancer - Rahman, Adiputra (Universitas Bojonegoro, 2023)
Cancer is a disease resulting from abnormal cell growth that leads to malignant neoplasms. Carcinoma Mammae (Ca Mammae) is a term for breast cancer which is characterized by the growth of malignant tumors in the breast tissue. Breast cancer is the main killer of women in the world, this is because every year there have been more than 1,000,000 cases in the world. Treatment of breast cancer is generally carried out through surgery which, if necessary, chemotherapy or radiation is a follow-up treatment. Therefore, early treatment with a variety of medicinal plants is an additional hope for controlling this breast cancer so that it can finally recover completely. The potentially medicinal compounds contained in noni fruit (Morinda citrifolia L.) include anthraquinones and quercetin, which play a role in inhibiting the development of cancer cells. This study aims to compare the potential of anthraquinones and quercetin from Morinda citrifolia L. fruit in preventing and treating cancer with Doxorubicin as a control. This step consists of target ligand and protein preparation, molecular docking, and drug similarity testing based on the Lipinski rule. The results showed that the anthraquinone compound from Morinda citrifolia L. fruit had better and safer anticancer potential with the lowest binding affinity -7.5.